2012
DOI: 10.5414/cn107169
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic changes following hemodialysis initiation in patients with advanced chronic kidney disease and symptomatic heart failure with reduced ejection fraction

Abstract: Background: In patients without overt cardiac disease, the degree of left ventricular hypertrophy (LVH) gets worse following hemodialysis (HD) initiation; however, in patients with both advanced chronic kidney disease (CKD) and symptomatic heart failure (HF) with reduced ejection fraction (EF), the short-term effect of HD on LVH and LV geometry has not been examined. We hypothesized that left ventricular mass index (LVMI) would decrease following HD initiation in CKD patients with symptomatic HF. Methods: We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
(54 reference statements)
0
12
1
2
Order By: Relevance
“…In patients with ESRD and HF, the initiation of dialysis may have favorable effects on the heart structure, possibly due to decrease of fluid overload. In a recent retrospective echocardiographic study of 41 patients with advanced CKD and symptomatic HF with low LVEF, Ganda et al [170] found a significant reduction in LV mass index within a few months from the start of HD, although there was no change in LV shortening fraction.…”
Section: Treatmentmentioning
confidence: 99%
“…In patients with ESRD and HF, the initiation of dialysis may have favorable effects on the heart structure, possibly due to decrease of fluid overload. In a recent retrospective echocardiographic study of 41 patients with advanced CKD and symptomatic HF with low LVEF, Ganda et al [170] found a significant reduction in LV mass index within a few months from the start of HD, although there was no change in LV shortening fraction.…”
Section: Treatmentmentioning
confidence: 99%
“…Similarly, an increase in serum ionized calcium and reduction in acidemia after hemodialysis would be expected to exert positive ionotropic effect on heart. 15 LV fractional shortening (FS) also increased in study patients following hemodialysis but it was not statistically significant. A study done by Nixon et al had showed that these changes in left ventricular function produced by regular hemodialysis are the combined effects of decrease in end diastolic volume and increase in contractile state of left ventricle.…”
Section: Resultsmentioning
confidence: 87%
“…Diabetic autonomic neuropathy and hypertensive heart disease are also contributing factors (6). Fluid overload contributes to venous congestion (7). Long-term haemodialysis via arteriovenous access may be involved in the pathogenesis of pulmonary hypertension by affecting pulmonary vascular resistance and cardiac output (8).…”
Section: Resultsmentioning
confidence: 99%